2014
DOI: 10.1308/003588414x13814021679113
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic bilateral synchronous multicentric papillary renal cell carcinoma masquerading as bilateral multifocal pyelonephritis

Abstract: Pyelonephritis is defined as an inflammation of the kidney and renal pelvis. The diagnosis is usually clinical. Acute multifocal bacterial nephritis is a rare form of pyelonephritis that is more severe and sepsis is more common. We report a patient who presented with fever and right-sided abdominal pain associated with right flank tenderness, suggesting right acute pyelonephritis. Bilateral multifocal pyelonephritis was diagnosed on ultrasonography, radionuclide renal scintigraphy and computed tomography. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Karthikeyan et al reported sporadic bilateral papillary RCC masquerading as bilateral multifocal pyelonephritis. 11 Also, Boukhannous et al reported a unilateral RCC masquerading as pyelonephritis. 3 Like Boukhannous et al, our patient had unilateral papillary RCC presenting with features of pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karthikeyan et al reported sporadic bilateral papillary RCC masquerading as bilateral multifocal pyelonephritis. 11 Also, Boukhannous et al reported a unilateral RCC masquerading as pyelonephritis. 3 Like Boukhannous et al, our patient had unilateral papillary RCC presenting with features of pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cases have been reported where unilateral or bilateral RCC has presented as pyelonephritis in elderly males. Karthikeyan et al reported sporadic bilateral papillary RCC masquerading as bilateral multifocal pyelonephritis 11 . Also, Boukhannous et al reported a unilateral RCC masquerading as pyelonephritis 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is feasible and safe in clinical application. Since BSSRCC is a rare disease [ 13 , 14 ], the longer follow- up period, more patient enrolment, and novel anatomic classification systems [ 15 ] are needed to further investigate the beneficial effects of different surgical approaches for the patients.
Fig.
…”
Section: Discussionmentioning
confidence: 99%